The significance of chinatown development to a multicultural america : an exploration of the Houston chinatowns - Zheng, Zen Tong Chunhua; Zou, Yali (Emerald points., 2023)
The Houston Chinatown's dramatic transformation from a Chinese enclave decades ago to a continually expanding multiethnic boomtown today contrasts development stagnation in many other traditional American Chinatowns. This pioneer study delineates the evolution of Houston's two Chinatowns, from the emergence and decline of Old Chinatown to the subsequent development and vibrant growth of New Chinatown - spanning nearly a century. Zheng and Zou delve into the distinctive character of New Chinatown, underscoring its innovative progress that sets it apart from the nation's oldest major Chinatowns, a quintessentially Houston story. They also probe the immigrant experience, political landscape, and socioeconomic dynamics that influenced the Chinatowns' metamorphoses. Scanning the community's collective response to the dire impact of the COVID-19 pandemic on New Chinatown, the chapters examine the latest development trends in the New Chinatown areas, shedding light on the extent to which they are upholding, or deviating from, traditional practices. Furthermore, the book explores the significance of these trends to the local community and beyond, alongside their wider implications. Amidst the growth challenges encountered by numerous Chinatowns across America, this timely work offers insightful perspectives on a sustainable model for urban and community development, as demonstrated by the transformative journey of Houston's New Chinatown.